Distribution system planning : evolution of methodologies and digital tools for energy transition /: evolution of methodologies and digital tools for energy transition. (2023) - Alvarez-Herault, Marie-Cecile; Gouin, Victor; Chardin-Segui, Trinidad; Malot, Alain; Coignard, Jonathan; Raison, Bertrand; Coulet, Jerome
No abstract available